Asian financial crisis and the evolution of Korean banks efficiency: a DEA approach - Sufian, Fadzlan; Habibullah, Muzafar Shah (Routledge, 2009)
In the mid-1990s, the East Asian countries experienced severe financial crisis that were followed by deep economic downturns. A variety of methodologies have been used to understand the nature of the Asian financial crisis. However, the impact of the 1997 Asian financial crisis on the efficiency of the financial industry has yet to be critically examined. By employing the Data Envelopment Analysis (DEA) approach the present study attempts to examine for the first time the impact of the 1997 Asian financial crisis on the efficiency of the Korean banking sector. The study focuses on three major approaches, namely, intermediation, value added, and operating approaches. The results clearly bring forth the high degree of inefficiency in the Korean banking sector, particularly a year after the Asian financial crisis. We find that the Korean banking sector has consistently exhibit higher technical efficiency levels under value added approach, while technical efficiency seems to be lowest under intermediation approach.